2023
DOI: 10.24114/jg.v15i2.45017
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Characteristics in Southern Waters of Java - Indonesia

Bachtiar W. Mutaqin,
Renny Laksmita Ningsih

Abstract: Detailed information regarding tidal characteristics in Indonesian waters is not yet available evenly, including in the southern waters of Java. Tides are one of the most essential hydro-oceanographic parameters in water dynamics. Therefore, this study aims to analyze the characteristics of the tides in the southern waters of Java, starting from Banten Regency in West Java to Malang Regency in East Java. Tidal data with measurement intervals every one hour were collected from December 23, 2022, to January 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Benoa Waters tidal data obtained from UHSLC produces harmonic constant values using the least square method, which is the value of amplitude and phase latency, including S0, M2, S2, N2, K2, K1, O1, P1, M4, and MS4, the results of which will then be used as parameters to find the Formzahl score [8]. So that the type and characteristics of tides in Benoa Waters can be known in the following Table From the results of these observations, it can also be found that the Formzahl score is 0.414, this score means that Benoa waters has a mixed-semidiurnal type [9].…”
Section: Resultsmentioning
confidence: 99%
“…Benoa Waters tidal data obtained from UHSLC produces harmonic constant values using the least square method, which is the value of amplitude and phase latency, including S0, M2, S2, N2, K2, K1, O1, P1, M4, and MS4, the results of which will then be used as parameters to find the Formzahl score [8]. So that the type and characteristics of tides in Benoa Waters can be known in the following Table From the results of these observations, it can also be found that the Formzahl score is 0.414, this score means that Benoa waters has a mixed-semidiurnal type [9].…”
Section: Resultsmentioning
confidence: 99%
“…This can be caused by many factors, either natural or human-induced. Various natural variables, such as tides, waves, coastal currents, water level, changes in wind direction, storms, and hurricanes-cyclones events, can impact coastal dynamics in the form of erosion and sedimentation (Clifton, 2003;Marfai et al, 2022;Morner, 2017;Mutaqin, 2017;Mutaqin & Ningsih, 2023). The presence of sea walls and other buildings can also affect it (Bird, 2019;Marfai et al, 2022).…”
Section: Resultsmentioning
confidence: 99%